Chapter Digesting the foreign. Food and Eating in the works of Tawada Yōko - Barbieri, Francesco Eugenio (Studi e saggi, 2021)
This paper aims at analyzing the representation of food and eating in seminal works by Japanese author Tawada Yōko. The first part of this contribution will analyze the connection between food and metamorphosis, focusing especially on Das Bad and Yogisha no yakōressha, works that belong to an earlier stage of the production of Tawada. The second part of this contribution will specifically inspect the representation and the metaphor of food in the works written in the aftermath of the 3.11 such as Kentōshi, Fushi no shima and the poem Hamlet no see.